The Effect of Performance-Based Budgeting, Regional Financial Management and Quality of Human Resources on SKPD Performance with Regional Financial Supervision as a Moderating Variable - Rio Johan; Afifah Rahmawati (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
This study’s objectives is investigating and analyzing how regional financial supervision can effect performance-based budgeting, regional financial management, and human resource quality on SKPD performance. The sample and population of this resesarch were the Regional Work Units (SKPD) in the DKI Jakarta area, with a total of 246 copies dispersed to the Regional Work Units (SKPD) in the DKI Jakarta area. SmartPLS (Partial Least Squares) software is used. The hypothesis test results in this resesarch show that performance-based budgeting has a positive impact on SKPD presentation, regional financial management has a positive impact on SKPD, human resource quality has no effect on SKPD performance, regional financial supervision has a positive and significant impact, regional financial supervision has a negative and not significant impact which cannot give impact porformances based budgeting on SKPD, and Moderation has no effect on SKPD performance, regional financial supervision moderation can strengthen the influence of regional financial management on SKPD performance, and regional financial supervision moderation has a negative and insignificant effect, which means it cannot strengthen the influence of human resource quality on SKPD performance. the result of this research suggest that you are be able to broaden the sample and population to investigate if changes in regional financial supervision can improve the influence of human resource quality on SKPD performance.